Extremely early initiation of vasopressors might not decrease short-term mortality for adults with septic shock: a systematic review and meta-analysis - Cheng-Hsin Ma; Jack Healy; Ebrima Kinteh; Cheng-Chin Ma; Ching-Fang Tiffany Tzeng; Eric H. Chou; Chin-Chieh Wu; Shih-Chieh Shao; Kuan-Fu Chen (Annals of Intensive Care)
Abstract Background The optimal timing for initiating vasopressor therapy in patients with septic shock remains unclear. This study aimed to assess the impact of early versus late vasopressor initiation on clinical outcomes. Methods A systematic review and meta-analysis were conducted by searching PubMed, Embase, and Cochrane databases. Studies comparing early and late vasopressor administration in septic shock patients were included. The primary outcome was short-term mortality, and subgroup analyses were performed based on different initiation timings. Results Eleven studies with 6,661 patients were included. Different studies define the ‘early administration’ timeframe variously, ranging from one to seven hours. No significant difference in short-term mortality was observed between early and late administration in the combined analysis of 3,757 patients from two RCTs and three quasi-experimental studies (OR: 0.66, 95% CI: [0.36, 1.19], I²: 82%). However, lower mortality was found in subgroups with early but not extremely early initiation (one to three hours, OR: 0.70, 95% CI: [0.60, 0.82], I²: 0%), and those using septic shock diagnosis as time zero (OR: 0.64, 95% CI: [0.48, 0.85], I²: 39%). Conclusion Our findings found that earlier initiation of vasopressor therapy, particularly within one to three hours after the diagnosis of septic shock, may be associated with reduced short-term mortality in certain subgroups. However, due to the heterogeneity in study definitions and potential confounding factors, these results should be interpreted cautiously. Further standardized investigations are warranted to precisely determine the optimal timing for vasopressor initiation to maximize survival outcomes in patients with septic shock.